The effects of personal data management on competition and welfare - Jiajia Cong; Noriaki Matsushima (Osaka University, Institute of Social and Economic Research (ISER), 2023)
This study examines how consumers' personal data management affects firms' competition in the data collection and data application markets and welfare outcomes. Consumers purchase products from differentiated firms in two markets. Firms compete to collect consumer data first to predict their preferences in the data application market, where each firm offers personalized prices to its targeted consumers and a uniform price to untargeted consumers. Before firms offer prices, their targeted consumers can erase data to become untargeted for a fixed cost. We show that consumers' privacy management mitigates price competition, reduces firms' profits, and harms consumer surplus and social welfare in the data application market; privacy management intensifies competition and improves consumer surplus in the data collection market. Across these two markets, profits and social welfare decline. The change in consumers' two-market surplus depends on their foresight regarding the outcomes in the data application market, with only forward-looking consumers having a higher surplus. We extend the model in several directions, including data-enabled product personalization, privacy costs, data portability, and data ownership, and discuss the implications for privacy laws.
Keywords: D11; D43; D62; L13; L51; 330; privacy management; data collection; data application; price discrimination; privacy laws